Line of sight model for visible light communication using Lambertian radiation pattern of LED. (21st December 2016) - Bhalerao, M.V.; Sumathi, M.; Sonavane, S.S.
Summary: This paper illustrates line of sight model for visible light source and a photodiode in wireless communication. Light‐emitting diodes (LEDs) are predominantly used everywhere like in houses and factories as light source due to development in technology of light sources.Haitz's law predicts an exponential rise in light output and efficiency of LEDs over a period of time. Light‐emitting diodes are having an average life of 50 000 hours with efficiency of 140 lm/W. Light‐emitting diode light sources are used for an eco‐friendly world due to its advantages over conventional wireless communication systems. For communication purpose in the visible light range, the LED and photodiode are used. A visible light communication system with LED as the transmitter and photodiode as the receiver is simulated in MATLAB for line of sight and analyzed using a Lambertian radiation pattern with a different mode number, field of view, and half power angle. Abstract : For communication purpose in the visible light range, the LED and photodiode are used. A visible light communication system with LED as the transmitter and photodiode as the receiver is simulated in MATLAB for line of sight and analyzed using a Lambertian radiation pattern with a different mode number, field of view, and half power angle.